PERAN PENYULUH PERTANIAN DALAM MEMAMPUKAN PETANI DALAM MENGELOLA USAHATANI CABAI MERAH DI DESA LASALEPA KECAMATAN LASALEPA KABUPATEN MUNA - Hasniawati Hasniawati; Rosmawaty Rosmawaty; Sitti Nur Isnian (Universitas Halu Oleo, 2022)
This study aims to: determine (1) the ability of farmers in red chili farming in Lasalepa Village, Lasalepa District, Muna Regency. (2) the role of agricultural extension workers on the ability of farmers to manage chili farming in Lasalepa Village, Lasalepa District, Muna Regency. This research was conducted in Lasalepa Village, Lasalaepa District, Muna Regency from June to November 2021, which was determined purposively with a total of 19 informants consisting of 11 main informants namely extension workers and 8 supporting informants namely farmers, this informant was determined purposively. ). The data in this study were processed using qualitative descriptive data analysis to determine the role of agricultural extension workers on the ability of farmers to manage red chili farming in Lasalepa Village, Lasalepa District, Muna Regency. The results showed (1) The ability of farmers in farming red chili in Lasalepa Village, Lasalepa District, Muna Regency is still low, this can be seen in the ability of farmers in land management caused by the ability of farmers which until now has not been maximized, so there is a need for the role of agricultural extension workers. as a facilitator, motivator, educator and dynamist; (2) The role of agricultural instructors on the ability of farmers to manage chili farming in Lasalepa Village, Lasalepa District, Muna Regency, the ability and motivation of chili farmers in Lasalepa Village, Lasalepa District, Muna Regency. Farmers really need the presence of agricultural extension workers as mediators, educators, motivators and dynamists in managing red chili farming in Lasalepa Village, Lasalepa District, Muna Regency.